Thermal ecology, activity pattern, habitat, and microhabitats used by the skink Mabuya arajara (Squamata: Scincidae) in the Araripe Plateau, northeastern Brazil - Ribeiro, Samuel Cardozo; Teles, Diego Alves; Mesquita, Daniel Oliveira; Almeida, Waltécio de Oliveira; Anjos, Luciano Alves dos [UNESP]; Guarnieri, Miriam Camargo (Taylor & Francis, 2019)
We evaluated the activity period, thermal ecology, habitats, and preference for microhabitats of the skink Mabuya arajara in a humid forest environment on the slope of the Araripe Plateau, Brazil. A total of 283 lizards were observed. The lizards were found to be diurnally active (unimodal type pattern), with peak activity during the hottest hours of the day (1100 to 1200). About habitat use, the majority of individuals (73.8% N = 209) were recorded in the narrow transitional area, in the edges of the forest; while 26.4% of individuals were observed in open areas and no observations were made in dense forest. Seven different types of microhabitats were used, with fallen palm leaves (Arecaceae) being the preferred (47.7% N = 135). Considering all lizards, microhabitat niche breadth was 3.27. Males and females presented a high overlap (0.95) in microhabitat use. The average Tc recorded for M. arajara was 32.06 ± 2.72°C. Body size (SVL) did not influence body temperature (F = 0.51, P = > 0.05). Most of the animals were observed with their bodies completely exposed (67.84%, N = 192), 18.37% (N = 52) were semi-exposed and 13.79% (N = 39) were in shelters. Among animals with some degree of sunlight exposure, 57.59% (N = 163) were in shadows, 25.10% (N = 71) were under sunlight filtered by vegetation, and 17.31% (N = 49) were under direct sunlight.A review of the ecology of Mabuya spp. shows that several features appear to be conserved among members of the genus.
Keywords: Chapada do Araripe; Copeoglossum arajara; Lizard; Natural History; Thermoregulation